Decontamination of Tomato Brown Rugose Fruit Virus-Contaminated Shoe Soles under Practical Conditions - Jens Ehlers; Shaheen Nourinejhad Zarghani; Bärbel Kroschewski; Carmen Büttner; Martina Bandte (Horticulturae, 2022)
Due to its global spread, easy mechanical transmissibility inside greenhouses, and detrimental effects on marketability, Tomato brown rugose fruit virus (ToBRFV) is considered to be one of the biggest threats to tomato production. Regarding such crop epidemics, it is essential to identify all conceivable transmission routes and to interrupt them with effective decontamination strategies. We analyzed the potential efficacy of reliable shoe sole cleaning in combination with a disinfection measure. For this purpose, first, a suspension test was undertaken that involved applying different disinfectants to an infected plant homogenate. This was followed by a simulated carrier test. Finally, shoe-sole decontamination was tested under practical conditions. The extent of decontamination was determined by bioassays of the infectivity of the initial load remaining after treatment. Thereby, necrotic local lesions on the susceptible indicator plant Nicotiana tabacum cv. Xanthi NN were counted. Recommendations for practical applications, based on suspension or simulated carrier tests, are limited in their applicability, since very short contact times between ToBRFV and disinfectants reduce efficacy. Under practical conditions, the approved disinfectant MENNO Florades was able to achieve complete inactivation of the virus in the disinfection mat following mechanical depletion from the shoe soles.